2013
DOI: 10.1103/physrevd.88.081301
|View full text |Cite
|
Sign up to set email alerts
|

Stability of super-Chandrasekhar magnetic white dwarfs

Abstract: It has been recently proposed that very massive white dwarfs endowed with strongly quantizing magnetic fields might be the progenitors of overluminous type Ia supernovae like SN 2006gz and SN 2009dc. In this work, we show that the onset of electron captures and pycnonuclear reactions in these putative super-Chandrasekhar white dwarfs may severely limit their stability.Comment: 5 pages, revised versio

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 39 publications
3
85
0
Order By: Relevance
“…The inner region of white dwarfs, in particular for B int 10 17 G, would have been neutronized if the drip density had not been changed with the field. Note that some authors have questioned the existence of such white dwarfs [14]. For example, the authors have argued that for the white dwarfs to be stable against neutronization, the magnetic field at the center should be less than few times 10 16 G for typical matter compositions.…”
Section: Discussionmentioning
confidence: 99%
“…The inner region of white dwarfs, in particular for B int 10 17 G, would have been neutronized if the drip density had not been changed with the field. Note that some authors have questioned the existence of such white dwarfs [14]. For example, the authors have argued that for the white dwarfs to be stable against neutronization, the magnetic field at the center should be less than few times 10 16 G for typical matter compositions.…”
Section: Discussionmentioning
confidence: 99%
“…In a related context, some authors [17] have suggested that the onset of neutronization and pycnonuclear reactions may limit the stability of the concerned super-Chandrasekhar white dwarfs, due to a softening of the underlying EoS. We recall here that a similar softening is brought about when a constant ρ B is added to ρ, without changing the pressure, while solving for the structure of the white dwarf.…”
mentioning
confidence: 92%
“…However, this is equally valid for nonmagnetized Chandrasekhar's white dwarfs whose central ρ is ∼ 10 9 gm/cc as well. The authors [17] further show that for the white dwarfs to be stable against neutronization, B at the center should be less than few times 10 16 G for typical matter compositions. Note that, as mentioned before at the end of §5, for B cent 10 16 G the mass-radius relation already starts approaching the limiting mass, yielding super-Chandrasekhar white dwarfs with mass 2.44M ⊙ , in the Newtonian regime itself.…”
mentioning
confidence: 99%
“…On the other hand, Hillebrandt, Sim & Röpke (2007) and Hachinger et al (2013) have argued that the explosion of a rotating super-M Ch WD will not necessarily produce the inferred nickel mass, or other characteristics, of such bright events, and they have suggested asymmetric explosions instead (see also Moll et al 2013). Chamel, Fantina & Davis (2013) have shown that another proposed means of supporting super-M Ch WDs, via ultra-strong quantizing magnetic fields, is impractical, due to electron-capture reactions that would make the WD unstable.…”
Section: Double Detonations and Rotating Super-chandrasekhar-mass Modelsmentioning
confidence: 99%